Artery of Percheron infarct - A missed opportunity of stroke thrombolysis - Naik, Milind; Dubey, Parul; Nilajkar, Gauri (Indian Journal of Case Reports, 2018)
Acute ischemic infarction in the territory of the artery of Percheron (AOP). AOP is a relatively uncommon neurovascular anatomical variant of the posterior circulation. It is a single arterial trunk supplying bilateral paramedian thalami and the rostral midbrain, a crucial structure responsible for regulation of alertness, consciousness, and sleep. The clinical presentation may deviate from the typical sensorimotor deficits seen with classical stroke syndromes. Without a high index of suspicion, AOP infarcts can be missed clinically and radiologically, thereby missing the crucial window of thrombolytic therapy. We discuss a case of a 60-year-old male, who was presented with acute onset altered sensorium due to AOP infarction and missed the opportunity for intravenous thrombolysis due to delayed diagnosis.